Repositioning Pesantren in Islamic Economics: From Educational Authority to Socio-Economic Enterprise - Zaenol Hasan; Kafa Nial Agil Eltamamy; Khamdan Rifa'i; Mahmudah Mahmudah; Endang Susilawati (FALASIFA : Jurnal Studi Keislaman, 2026)
This study examines the transformation of pesantren within the framework of Islamic economics, focusing on their repositioning from traditional religious-educational institutions into socio-economic enterprises. While previous studies have primarily emphasized the educational and da‘wah functions of pesantren, limited attention has been given to their expanding economic roles and institutional transformation. To address this gap, this study employs a qualitative library research design using a text-based analytical approach. The analysis draws upon academic literature, institutional perspectives, and regulatory frameworks, particularly Law Number 18 of 2019 concerning Pesantren. The findings reveal that pesantren are increasingly integrating economic functions into their institutional structures through the establishment of cooperatives, micro-enterprises, entrepreneurial initiatives, and sharia-compliant financial activities. This development reflects the emergence of a hybrid institutional model that combines religious authority, educational functions, and socio-economic engagement within a single organizational framework. The study further demonstrates that pesantren contribute to broadening the scope of Islamic economics by promoting community-based, ethically grounded, and socially embedded economic practices. In addition, legal recognition has played a significant role in legitimizing and strengthening pesantren’s economic transformation, although challenges related to governance, managerial capacity, and institutional sustainability remain substantial. This research contributes to the discourse of Islamic economics by conceptualizing pesantren as socio-economic enterprises and by offering an alternative perspective on Islamic economic institutions that emphasizes social empowerment, ethical orientation, and community resilience.